Can Pin-on-Disk Testing Be Used to Assess the Wear Performance of Retrieved UHMWPE Components for Total Joint Arthroplasty?. (11th September 2014) - Kurtz, Steven M.; MacDonald, Daniel W.; Kocagöz, Sevi; Tohfafarosh, Mariya; Baykal, Doruk
Abstract : The objective of this study was to assess the suitability of using multidirectional pin-on-disk (POD) testing to characterize wear behavior of retrieved ultrahigh molecular weight polyethylene (UHMWPE). The POD wear behavior of 25 UHMWPE components, retrieved after 10 years in vivo, was compared with 25 that were shelf aged for 10–15 years in their original packaging. Components were gamma sterilized (25–40 kGy) in an air or reduced oxygen (inert) package. 9 mm diameter pins were fabricated from each component and evaluated against CoCr disks using a super-CTPOD with 100 stations under physiologically relevant, multidirectional loading conditions. Bovine serum (20 g/L protein concentration) was used as lubricant. Volumetric wear rates were found to vary based on the aging environment, as well as sterilization environment. Volumetric wear rates were the lowest for the pins in the gamma inert, shelf aged cohort. These results support the utility of using modern, multidirectional POD testing with a physiologic lubricant as a novel method for evaluating wear properties of retrieved UHMWPE components. The data also supported the hypothesis that wear rates of gamma-inert liners were lower than gamma-air liners for both retrieved and shelf aging conditions. However, this difference was not statistically significant for the retrieved condition.